Oral pigmentations in Laugier-Hunziker syndrome: a case report and review of diagnostic criteria - Luiz Arthur B. Silva; Rodrigo P. Mafra; Patrícia T. Oliveira; Ana Miryam C. Medeiros; Leão P. Pinto; Éricka Janine D. Silveira (Sociedade Brasileira de Patologia Clínica, 2018)
ABSTRACT Laugier-Hunziker syndrome (LHS) is a rare mucocutaneous disorder, of unknown etiology, characterized by multiple hyperpigmented macules, dispersed mostly on the oral mucosa, occasionally associated with longitudinal ridging of the nails. The diagnosis requires exclusion of other conditions, such as Addison's disease and Peutz-Jeghers syndrome. We report a case of a 34-year-old male patient, presenting with hyperpigmented macules on the lips, buccal mucosa and palate, as well as mild dark striations on toenails. After careful clinical and laboratorial investigations, the diagnosis of LHS was established. Given the lack of aesthetic complaints and symptoms, no treatment was necessary.